Marketing Channels Of Tomatoes (Solanum Lycopersicum L.) In Argoayuningtani Farmers' Group, Senden Village, Selo District, Boyolali District - Andika; Prasetyo, Agung; Irawan, Norbertus Citra (Journal of Rural and Urban Community Studies, 2024)
This study aims to (1) determine the tomato marketing channels (2) determine the level of tomato marketing margins in each marketing channel (3) determine the efficiency of tomato marketing in each marketing channel. The method used is the quantitative descriptive method. The research implementation method is the survey method. The method of selecting the research location is done intentionally (purposive). The method of determining farmer samples using the total sampling technique and determining marketing institution samples using the snowball sampling technique. The data analysis method is carried out using marketing margin analysis and marketing efficiency analysis. The results of the study showed that there were two tomato marketing channels in the Argoayuningtani Farmer Group, namely the first tomato marketing channel starting from farmers to collectors then to wholesalers then to retailers then to consumers and the second marketing channel starting from farmers to retailers then to consumers. Marketing channel I obtained a marketing margin of Rp 11,000 / kg with an efficiency level of 16.84%. Marketing channel II obtained a marketing margin of Rp 6,000 / kg and a marketing efficiency level of 7.81%.